2019
DOI: 10.1259/bjr.20181034
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuity of suspicious breast lesions on contrast enhanced breast CT compared to digital breast tomosynthesis and mammography

Abstract: Unlike conventional two-dimensional (2D) digital mammography (DM) and digital breast tomosynthesis (DBT), dedicated breast CT (bCT), an emerging technology, provides fully three-dimensional isotropic image data sets without the need for breast compression. Unenhanced dedicated bCT has been shown in prior studies to be superior to mammography for the detection of masses but not microcalcifications. 1 More recently, contrast-enhanced dedicated bCT (CEbCT) was reported as a potential method for differentiating ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Indeed, the volumetric (lateral and depth resolution) rendition of the breast should be assured, which is possible in practice by deriving 3D phantoms from fully 3D examinations as those produced via BCT. 21,[37][38][39][40] However, unlike the widespread utilization of routine examinations in DM and DBT, only,~1000 patients have been scanned with BCT (mainly at UC Davis and University of Rochester medical centers) 31,[41][42][43][44] and for the produced dataset this aspect can affect the representativeness of a large patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the volumetric (lateral and depth resolution) rendition of the breast should be assured, which is possible in practice by deriving 3D phantoms from fully 3D examinations as those produced via BCT. 21,[37][38][39][40] However, unlike the widespread utilization of routine examinations in DM and DBT, only,~1000 patients have been scanned with BCT (mainly at UC Davis and University of Rochester medical centers) 31,[41][42][43][44] and for the produced dataset this aspect can affect the representativeness of a large patient population.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing a dedicated contrast‐enhanced (ce) breast CT scan with mammography, studies have shown that detection rates for malignant lesions were significantly better on contrast‐enhanced breast CT 8 . Microcalcifications were seen better on ce breast CT than on nonenhanced breast CT but similarly on mammography 8,9 . Also, malignant lesions showed a more profound enhancement than benign lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Iliya Dyakov 1 , Simona Avramova-Cholakova 2 , James O'Sullivan 2 1 Acibadem City Clinic, Sofia, Bulgaria; 2 Imperial College Healthcare NHS Trust, London, UK Purpose: The purpose of the present study is to compare different methods for effective dose (E) estimation of patients that have undergone several CT examinations with cumulative effective dose (CED) of 100 mSv and above. Material and Methods: Patient data were retrospectively extracted using a dose management software (DMS).…”
Section: Comparison Of Different Methods For Calculation Of Patient Ementioning
confidence: 99%
“…. [1][2][3] Virtual clinical trials (VCT) are an alternative approach to real clinical trials, capable of producing clinical outcome data as it relates to new imaging technology without the added cost and complexity of real clinical trials. VCT are in-silico reproductions of real examinations, which adopt digital models of patients and simulated apparatuses.…”
Section: 67mentioning
confidence: 99%